The diminished effect of women’s entrepreneurial self-efficacy on firm performance - Glosenberg, Alex; Ward, M.K.; Pollack, Jeffrey (2019)
The purpose of this study is to test whether the relationship between entrepreneurial self-efficacy (ESE) and firm performance is lower for women than for men due to socioeconomic factors related to gender. To test our hypothesis, we conducted a meta-analysis and meta-analytic regression. Altogether, 92 relevant effect sizes were identified and included in the meta-analysis. Our hypothesis was supported (β=-.35, b=-.05, SE=.02, p=.016) with lower effect sizes tending to predominate among studies of more women. This study provides evidence of limitations to the generalizability of the strength of the relationship between ESE and firm performance.